2021
DOI: 10.3390/insects12090801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feed Containing Hermetia illucens Larvae Immunized by Lactobacillus plantarum Injection on the Growth and Immunity of Rainbow Trout (Oncorhynchus mykiss)

Abstract: We investigated the effects of a feed containing Hermetia illucens larvae injected with bacteria on the growth and immunity of Oncorhynchus mykiss. The feed was prepared by replacing fishmeal in feed with 25 and 50% nonimmunized (HIL25, HIL50) or immunized HIL (ImHIL25, ImHIL50), and its protein:fat:carbohydrate ratio was 45:15:18. ImHIL extracts showed inhibitory activity against fish pathogenic bacteria. Both red blood cell count and insulin-like growth factor-1 as the growth indicator were the highest among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…These obstructions, especially chitin, severely limited the utilization of BSF as FM substitution in the feed industry. A study on rainbow trout revealed that 15% BSF in the diet is the maximum addition for fish growth [24]; adding 25% BSF into catfish meal is the maximum of having no negative effect on growth rate and nutrition utilization efficiency [25]. Previously, we found that the content of chitin in the BSF larva cuticle rose from 3% to 84% from larva to prepupa.…”
Section: Introductionmentioning
confidence: 92%
“…These obstructions, especially chitin, severely limited the utilization of BSF as FM substitution in the feed industry. A study on rainbow trout revealed that 15% BSF in the diet is the maximum addition for fish growth [24]; adding 25% BSF into catfish meal is the maximum of having no negative effect on growth rate and nutrition utilization efficiency [25]. Previously, we found that the content of chitin in the BSF larva cuticle rose from 3% to 84% from larva to prepupa.…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, dose-dependent trends in survival, against both Flavobacterium columnare and Streptococcus iniae challenges, were observed, suggesting that dietary frass from black soldier fly larvae could be beneficial by improving innate immunity and disease resistance of hybrid tilapia against bacterial infection. In an innovative study, black soldier fly larvae were injected with bacteria to boost insect immunity and then incorporated in diets for rainbow trout [144]. Dietary treatments included fishmeal replacement by 25 or 50% of non-immunised or immunised black soldier fly larvae meals.…”
Section: Impacts Of Alternative Protein Sources On Immune Function An...mentioning
confidence: 99%
“…Among the insects, the black soldier fly (BSF) ( Hermetia illucens , Linnaeus 1758, Diptera, Stratiomyidae family) and its larvae, which are native to the tropical, subtropical, and warm temperate areas of Southern United States (three generation cycles per year) have been shown to be a good replacement of FM and FO ( Hoc et al, 2019 ). In this regard, feed incorporated with different combinations of BSF led to the best overall response in terms of growth and health in trout ( Huyben et al, 2019 ; Fawole et al, 2021 ; Bolton et al, 2021 ; Caimi et al, 2021 ; Hoc et al, 2021 ; Hwang et al, 2021 ; Melenchón et al, 2021 ; Randazzo et al, 2021 ; Cho et al, 2022 ; Liu et al, 2022 ; Ratti et al, 2023 ), salmon ( Belghit et al, 2019 ; Li et al, 2019 ; Weththasinghe et al, 2021 ), clownfish ( Vargas-Abúndez et al, 2019 ), zebrafish ( Zarantoniello et al, 2018 ; Zarantoniello et al, 2019 ), seabass ( Wang et al, 2019 ; Moutinho et al, 2021 ), tilapia ( Yildirim-Aksoy et al, 2020b ; Tippayadara et al, 2021 ; Agbohessou et al, 2022 ), catfish ( Xiao et al, 2018 ; Adeoye et al, 2020 ; Yildirim-Aksoy et al, 2020a ; Sudha et al, 2022 ), and shrimp ( Cummins Jr et al, 2017 ; Yildirim-Aksoy et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%